Effects of paddy field non-grainization consolidation on sustainable eco-functions protection of soil bacterial: Empirical evidence from Zhejiang province, China - Liang, Ying; Geng, Bin (Frontiers in Environmental Science, 2023)
Non-grain phenomenon of paddy field which become a severe threat to food security and agricultural sustainable development has attracted great attention in China. Since 2020. Soil bacterial communities play a crucial role in driving a variety of ecosystem functions and ecological processes, and is the main driving force to maintain the biogeochemical cycle. Research focus is urgently needed on the effects of large-scale paddy field non-grainization consolidation on soil bacteria and sustainability of ecological functions in southern China. Therefore, elucidating the patterns of change in soil bacterial communities and ecological functions before and after paddy field NGC can provide important support for sustainable conservation of paddy field soil ecosystem. This study examined soil samples before and after paddy field NGC in Zhejiang , China, measured soil environmental factors and performed 16S rDNA amplicon sequencing to analyze the changes in soil bacterial communities and ecosystem functions before and after NGC. Our findings indicated that: NGC increased the relative abundances of Proteobacteria(27.89%) and Actinobacteria(25.25%) in the project zones, Proteobacteria increased significantly after implementation in project zones 01, 02 and 09. Actinobacteria increased markedly in project zones 03, 04, 08, and 09. In terms of absolute soil bacterial community content, total soil bacteria increased in all project area samples after NGC implementation, with the largest increase in project zone 07 (74.18%) and the smallest increase in project zone 05 (3.05%). Proteobacteria, increased markedly after implementation in project zones 01, 02, 03, 05, 06, 07 and 09. NGC led to improvements in alpha diversity indices, including Ace, Chao1, Coverage, and Shannon indices(p<0.01) in terms of soil bacterial community diversity. The data analysis of RDA and the significance test showed that the environmental factors which were close-knitted with the soil bacterial diversity and structure of the sample sites were TN, pH, SOM, FIQ, SMI , and AK . Wilcoxon rank sum test results showed that NGC also significantly enhanced the amino acid transport and metabolic functions of soil bacterial communities(p<0.01). In conclusion, NGC is beneficial to improve the soil bacterial diversity, enhance the versatility of soil ecosystems, and promote sustainable cultivated land soil ecosystem protection.